2019
DOI: 10.1007/s11883-019-0791-9
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Evidence that ApoC-III Inhibitors Provide Novel Options to Reduce the Residual CVD

Abstract: Purpose of Review Apolipoprotein C-III (apoC-III) is known to inhibit lipoprotein lipase (LPL) and function as an important regulator of triglyceride metabolism. In addition, apoC-III has also more recently been identified as an important risk factor for cardiovascular disease. This review summarizes the mechanisms by which apoC-III induces hypertriglyceridemia and promotes atherogenesis, as well as the findings from recent clinical trials using novel strategies for lowering apoC-III. Recent Findings Genetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 112 publications
(112 reference statements)
1
55
0
Order By: Relevance
“…However, this ASO was not approved by the FDA for the treatment of familial chylomicronemia syndrome due to adverse effects related to thrombocytopenia. The Committee for Medicinal Products for Human Use of the European Medicines Agency however, authorized conditional marketing for Waylivra (volanesorsen) as an adjunct to diet in adult patients with genetically confirmed familial chylomicronemia syndrome who are at high risk for pancreatitis, in whom response to diet and TG-lowering therapy has not worked (123). New formulations of APOC3 inhibitory drugs are likely to reduce side-effects.…”
Section: Emerging Strategies To Lower Hypertriglyceridemia and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this ASO was not approved by the FDA for the treatment of familial chylomicronemia syndrome due to adverse effects related to thrombocytopenia. The Committee for Medicinal Products for Human Use of the European Medicines Agency however, authorized conditional marketing for Waylivra (volanesorsen) as an adjunct to diet in adult patients with genetically confirmed familial chylomicronemia syndrome who are at high risk for pancreatitis, in whom response to diet and TG-lowering therapy has not worked (123). New formulations of APOC3 inhibitory drugs are likely to reduce side-effects.…”
Section: Emerging Strategies To Lower Hypertriglyceridemia and Theirmentioning
confidence: 99%
“…Human studies have firmly linked APOC3 to plasma TG levels ( 121 123 ). APOC3 is mainly produced by the liver and to a lesser extent, by the intestine.…”
Section: Animal Models Of Hypertriglyceridemia and Their Susceptibilimentioning
confidence: 99%
“…Furthermore, recent studies suggest that apolipoprotein C3 (APOC3), an apolipoprotein that prevents clearance of TRLs and their RLPs (14)(15)(16)(17)(18), predicts incident CVD in subjects with T1DM even when triglyceride levels are in the normal range or close to normal range (19,20). The effect of APOC3 as a CVD risk factor was independent of glycemic control (HbA1c levels).…”
mentioning
confidence: 99%
“…Consistent with a critical role for apoC-III, genome-wide association studies have shown that loss-of-function (LOF) variants of this protein are associated with reduced plasma TG levels [7][8][9] . These observations suggest that inhibition of apoC-III function should be of therapeutic benefit and there is much interest in developing suitable approaches 10 . In particular, reduction of apoC-III expression using an antisense oligonucleotide 11,12 and direct protein targeting with a monoclonal antibody 13 show promise.…”
Section: Introductionmentioning
confidence: 99%